2001
DOI: 10.1002/1522-2675(20010613)84:6<1889::aid-hlca1889>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motions in Crystalline Anthracene and Naphthalene from Multitemperature Diffraction Data

Abstract: Dedicated to Edgar Heilbronner, in adminationAtomic Displacement Parameters (ADPs) of anthracene (94 ± 295 K), (D 10 )anthracene (16, 295 K), naphthalene (92 ± 239 K), and (D 8 )naphthalene (12, 295 K) have been analyzed with the help of an Einsteintype model of local, molecular normal modes. The low-frequency motions are expressed in terms of molecular translations, librations, and deformations, and account for the temperature dependence of the experimental ADPs. Their frequencies decrease with increasing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…This analysis is carried out in the molecular inertial system and assumes rigid molecules. Bürgi et al showed the amplitudes of the intramolecular modes to be small compared with the rigid body motion 21 . Additionally, molecular dynamics studies indicate that in the energy range of interest the excited modes are to a high degree of intermolecular type 22 .…”
Section: Methodsmentioning
confidence: 99%
“…This analysis is carried out in the molecular inertial system and assumes rigid molecules. Bürgi et al showed the amplitudes of the intramolecular modes to be small compared with the rigid body motion 21 . Additionally, molecular dynamics studies indicate that in the energy range of interest the excited modes are to a high degree of intermolecular type 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Bü rgi and co-workers have recently described an elegant method for studying the dynamics of molecules in crystals through the analysis of multi-temperature neutron diffraction data (Bü rgi & Fö rtsch, 1999;Bü rgi & Capelli, 1999Bü rgi et al, 2001;Capelli et al, 2000). The normal modes derived from this approach incorporate both internal and external degrees of freedom, and can also be used to estimate the ADPs for any atom at any intermediate temperature (Bü rgi et al, 2002).…”
Section: Approximate Methods Combining Estimates Of Internal and Extementioning
confidence: 99%
“…Thermal expansion is closely connected to the correlated movements of these rigid bodies. It can be shown that the amplitudes of the intramolecular modes are much smaller than those of the rigid bodies (Bü rgi et al, 2001). The rigid body position itself is described by three eulerian angles and a position vector and its motion by a translation T tensor, a librational L tensor, and a coupling tensor S within the molecular inertial system I.…”
Section: Tls Temperature-dependent Description Of the Btbt-c4oh Moleculementioning
confidence: 99%